The Strategies for Managing Customer Value in Startups in Conditions of High Market Dynamics - Tonieva Krystyna V.; Shvets Anastasiia D.; Samus Pavlo O. (Bìznes Inform, 2025)
The article explores customer value management (CVM) strategies tailored for startups operating in conditions of high market dynamics and limited resources. The aim is to systematize effective approaches to maximizing customer lifetime value (CLV) to ensure sustainable growth for startups. The relevance arises from the need to shift from short-term attraction tactics to strategic management of relationships and the value of the customer base as a key asset of the startup. The research is based on the analysis and synthesis of scientific literature on CRM, CLV, startup marketing, and digital technologies. A systemic and comparative analysis of various CVM strategies (value-based segmentation, personalization, CXM, loyalty programs, and omnichannel strategies) and their applicability to startups has been used. The role of data analytics and agile approaches in implementing these strategies has been analyzed. Key CVM strategies adapted for startups have been identified: segmentation by CLV, personalization of offers, customer experience management, agile loyalty programs, integrated omnichannel interaction, and the use of analytics for decision-making. The importance of an integrated approach and continuous adaptation of strategies to market changes is underlined. Key performance indicators (CLV, CLV/CAC, Retention Rate, Churn Rate, NPS, CSAT) have been proposed for monitoring results. The article systematizes and adapts customer value management strategies to the specific conditions of startups, emphasizing the importance of a long-term perspective, flexibility, and the use of data. The practical value lies in providing startups with a structured overview of effective CVM strategies and KPIs to enhance competitiveness and ensure sustainable growth through a focus on customer value.